CD146, a novel target of CD44-signaling, suppresses breast tumor cell invasion - Allal Ouhtit (14153256) (2017)
We have previously validated three novel CD44-downstream positively regulated transcriptional targets, including Cortactin, Survivin and TGF-β2, and further characterized the players underlying their separate signaling pathways. In the present study, we identified CD146 as a potential novel target, negatively regulated by CD44. While the exact function of CD146 in breast cancer (BC) is not completely understood, substantial evidence from our work and others support the hypothesis that CD146 is a suppressor of breast tumor progression. Therefore, using molecular and pharmacological approaches both in vitro and in breast tissues of human samples, the present study validated CD146 as a novel target of CD44-signaling suppressed during BC progression. Our results revealed that CD44 activation could cause a substantial decrease of CD146 expression with an equally notable converse effect upon CD44-siRNA inhibition. More interestingly, activation of CD44 decreased cellular CD146 and increased soluble CD146 through CD44-dependent activation of MMP. Here, we provide a possible mechanism by which CD146 suppresses BC progression as a target of CD44-downstream signaling, regulating neovascularization and cancer cell motility. Other Information Published in: Cell Communication and Signaling License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s12964-017-0200-3